ANALISIS KONTRIBUSI SEKTOR KELAUTAN DAN PERIKANAN TERHADAP PRODUK DOMESTIK REGIONAL BRUTO KABUPATEN SUMBAWA - Yulistia Alwasifah; Sri Rahayu (Jurnal Ekonomi & Bisnis, 2022)
This study aims to know how much the contribution of the marine and fisheries sector toward the Gross Regional Domestic Product (PDRB) of Sumbawa District. This study was a descriptive. Types of data in this study were quantitative and qualitative. The data sourced used was secondary from 2010 until 2019 which was taken from the Central Bureau of Statistic (BPS) of Sumbawa District and literature related to this study. Data collection methods used were documentation and literature. Data analysis techniques used was contribution analysis. Based on the results of study showed that the contribution of the marine and fisheries sector toward gross regional domestic product if seen from the constant price was of 9.20% per year and from the current price of 8.59% per year. The amount of this contribution will have an impact toward the economy of the Sumbawa District. The higher contribution made, communities’ economy will also increase and in the end it will improve the regional economy of Sumbawa District.